The effect of visual perception training on sensorimotor function in handball players - Florkiewicz, B.; Fogtman, S.; Lesiakowski, P.; Zwierko, T. (Journal of Kinesiology and Exercise Sciences, 2015)
The present study is aimed at investigating the efficiency of a specific perceptual training program used to enhance visuomotor processing in athletes. Material and methods. The experimental group involved 15 university handball players. The control group included 13 nonathletic students. Both groups were homogeneous in terms of age and gender. The simple and differential reaction time included in the Vienna Test System (Schuhfried, Austria), eye-hand coordination test and visuospatial specific run test (Fitlight Sports Corp., Canada) were performed three times: before the experiment, after six weeks of perceptual training, and a retention test at intervals of four weeks. The perceptual exercise methodology was based on vision enhancement and specific visual-motor reaction training. Results. Following the training period, the majority of visuomotor parameters improved. The greatest effect was observed in the differential reaction time test (p<0.01), eye-hand coordination test (p<0.001) and visuospatial specific run test (p<0.001). Perceptual training does not affect the results of the simple reaction task (p>0.05). The results of the retention test confirmed the visual training effects. Conclusion. The six-week training period suggests that perceptual skills are trainable and can be improved by means of appropriate training. The positive effects obtained after a period of six weeks of training are limited. Proper implementation of the perceptual training program into sports practice in handball is recommended.